IFNAR1 gene mutation may contribute to developmental stuttering in the Chinese population - Yimin Sun (BMC, 2021)
Abstract Background Developmental stuttering is the most common form of stuttering without apparent neurogenic or psychogenic impairment. Recently, whole-exome sequencing (WES) has been suggested to be a promising approach to study Mendelian disorders. Methods Here, we describe an application of WES to identify a gene potentially responsible for persistent developmental stuttering (PDS) by sequencing DNA samples from 10 independent PDS families and 11 sporadic cases. Sanger sequencing was performed for verification with samples obtained from 73 additional patients with sporadic cases. Results We first searched for cosegregating variants/candidate genes in a Chinese family (Family 0) by sequencing DNA obtained from 3 affected members and 3 controls. Next, we sequenced DNA samples obtained from 9 additional Chinese families (Families 1-9) with stuttering to verify the identified candidate genes. Intriguingly, we found that two missense variants (Leu552Pro and Lys428Gln) of interferon-alpha/beta receptor 1 (IFNAR1) cosegregated with stuttering in three independent families (Families 0, 5 and 9). Moreover, we found two additional mutations (Gly301Glu and Pro335del) in the IFNAR1 gene in 4 patients with sporadic cases by using WES or Sanger sequencing. Further receptor mutagenesis and cell signaling studies revealed that these IFNAR1 variants may impair the activity of type I IFN signaling. Conclusion Our data indicate that IFNAR1 might be a potential pathogenic gene of PDS in the Chinese population.